Respon Imun Pada Penderita Asma Selama Kehamilan - Wiwik Agustina (Akademi Keperawatan Dharma Husada Kediri, 2015)
The immune system of a woman while pregnant it would be more sensitive than usual. Therefore, pregnant women are particularly vulnerable to some diseases, particularly influenza. A new study suggests that women who often experience flu during pregnancy, would be at risk of having children with asthma. In addition, asthma and allergies can also be inheritable. If both parents have allergies, the child has an allergy risk 75 percent. If only one parent with allergies, or if a near of kin has an allergy, the child will have a 30 to 40 percent risk of experiencing various types of allergies. However, if the parents do not have allergies at all, the risk of allergies in children only 10 to 15 percent. This scientific work aimed to determine the immune response in pregnant women with a asthma. This scientific work methods using literature study. Effect of pregnancy on the incidence of asthma attacks in each patient are not the same, even attacks are not common in a first pregnancy and subsequent pregnancies. Usually the attack will arise from the age of 24 weeks to 36 weeks, and will be reduced by the end of pregnancy. Effect of asthma in mother and the fetus is very dependent on the frequency and severity of asthma attacks, because of the mother and the fetus will experience hypoxia. Hypoxia if not addressed would have a detrimental effect on the fetus, such as miscarriage, premature delivery, and fetal weight were not in accordance with gestational age. It is expected the public to give more attention and be aware in patients with asthma, especially in during pregnancy. Keywords : immune system , pregnant women , asthma